REKONSTRUKSI PERAN POLITIK PEREMPUAN MENURUT MUSDAH MULIA - Zaprulkhan Zaprulkhan (IAIN Ponorogo, 2015)
Abstract: As if it never finished to talk about the role of women in the public sphere. This is because the role of women in the public sphere, particularly in their political role is considered to be less significant. Up to the third millennium, some scholars and intellectuals still had a negative view about the role of positive contribution of women in the political arena. They interpreted the Qor’an and the hadith (traditions of the Prophet, sayings of the Prophet) textually with which prohibited women involve in politics. Through constructive critics and holistic reconstruction, this study tried to explore the political role of women in the public sphere based on ‘notion’ of Musdah Mulia. According to Musdah, the important things that should be done was not only the reconstruction of the interpretation of the fundamental doctrines of Islam (Qur'an and Hadith), but also practical implementation in the fields of education, culture, and public policies. All reconstructions of woman role in political leadership should be carried out simultaneously in order to produce concrete changes. This is because there were a number of internal factors that had caused women not be able to play their role significantly in the political sphere that consisted of figure of women themselves who were unconfident and passive to the given opportunities they had. They also got lack of support; they were chained in stereotypes as guardians of household, and still confined by misogynistic tradition, as well as caused by the biased interpretation of religious doctrines related to the patriarchal values and gender domain. الملخص :كاد لا ينتهي الحديث عن دور المرأة في وسط المجتمع . وذلك لأن دورها فيه – وخاصة في المجال السياسي – قليل. وإلى هذا الحين لا يزال بعض العلماء والمثقفين نظروا إلى دور المرأة الإيجابي في وسط المجتمع نظرة سلبية. فسّر هؤلاء الآيات القرآنية والأحاديث النبوية الناهية المرأة عن الاشتراك في المجال السياسي تفسيرا حرفيا. حاولت هذه الدراسة – بمدخل نقدي بنّاء شامل – دراسة الدور السياسي للمرأة وسط المجتمع فكرة موسدة موليا. ترى موسدة أن العمل الواجب قيامه به هو، ليس فقط إعادة طريقة تفسير القرآن والحديث بل كذلك إيجاد الحركات في مجال التربية، والثقافة، والقرارات الإجتماعية. وجميع إعادة بناء لدور المرأة لابد أن تقام جماعية لتحقيق التغيّر الواقعيّ. وهذا لأن هناك عوامل داخلية للمرأة تمنع المرأة للتدخّل في المجال السياسي، وهي عدم ثقتها بنفسها وعدم انتهازها للفرصة الموجودة. وكذلك التأييد لها قليل، محبوسة في ضوء المقولة